An exploratory study into understanding behavioural change in respect of HIV/AIDS : a pre-test and post-test evaluation - Govender, Pavlin Jayasceelan; Du Toit, J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2002.